Unusual Localization of an Emergent Bacterium, Raoultella ornithinolytica - Michele Cavaliere; Guido Bartoletti; Pasquale Capriglione; Antonella Miriam Di Lullo; Gaetano Motta; Maurizio Iengo; Elena Cantone (Case Reports in Medicine)
Raoultella ornithinolytica is a bacterium belonging to the family Enterobacteriacae. It is a rare but emergent cause of human pathologies especially in immunocompromised patients. We described the first case in the literature of isolated external otitis sustained by Raoultella ornithinolytica in an immunocompetent host. A 54-year-old Caucasian man with a history of previous myringoplasty came to our attention reporting otalgia and otorrhea. We performed right ear swab for culture examination, meanwhile we started empirical therapy with topic administration of neomycin, without any clinical improvement. The cultural examination showed the presence of a Raoultella ornithinolytica infection. After ten days of treatment with oral ciprofloxacin and topic levofloxacin, there was the complete resolution of pain and inflammation. Raoultella ornithinolytica must be taken into consideration as an emergent cause of human infection, also in case of external otitis. Infection can be severe and can occur both in immunocompromised and in immunocompetent hosts. Culture test is mandatory to choose the proper therapy and avoid potential severe complications.